ANALISIS PENERAPAAN PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM ( Studi Penelitian Di SDN Nusawangi Tasikmalaya) - Jani Sanjari (HASBUNA : Jurnal Pendidikan Islam, 2024)
The curriculum has become the most important factor in education. The curriculum is a set of plans and arrangements of goals, content, material for learning activities and methods used as guidelines for organizing learning activities to achieve certain educational goals. All activities of learning activities for Learners at school form a great curriculum concept. The method used in this research uses qualitative methods. Qualitative method as a research procedure that presents descriptive data some written or spoken words from people or actors that can be observed. Implementation of differentiated learning in Islamic Religious Education subjects at SDN Nusawangi. PAI-BP educators have implemented differentiated learning as a learning strategy and learning method. Islamic Religious Education subject educators implement differentiated learning readiness-based processes by mapping based on the results of diagnostic assessments, but do not provide content that is a hierarchy of abilities possessed.The Impact of the Implementation of Differentiated Learning in Islamic Religious Education Subjects at SDN Nusawangi Tasikmalaya has positive and negative impacts, these impacts can come from students, and educators themselves. The implementation of differentiated learning by adjusting learning styles and content has a significant positive impact on both students and educators. Learners get more targeted learning and allow them to be themselves while learning. Meanwhile, educators feel happy because they can help learners learn according to their abilities, and allow expert learners to become peer tutors.